2001
DOI: 10.1021/jp012026y
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Solid-State Dye-Sensitized TiO2 Solar Cells:  Effective Charge Transport in Mesoporous Space Filled with Gel Electrolytes Containing Iodide and Iodine

Abstract: Quasi-solid-state dye-sensitized solar cells were fabricated using low-molecular-weight gelators. They showed comparable photoenergy conversion efficiencies to the liquid cell at high illumination intensity up to AM 1.5 (1 sun). Conductivity measurements of the electrolyte phases revealed that the gelation does not affect the conductivity of the electrolyte and that the conductivity increased with an increase of iodine in both gel electrolytes and liquid electrolyte. The formation of polyiodide ions, such as I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
276
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(290 citation statements)
references
References 44 publications
10
276
1
3
Order By: Relevance
“…[19,20] Previously it was found that incorporating the redox couple I /I 3 and higher polyidides into existing gel electrolytes by adding iodine increases the conductivity, which was attributed to Grotthuss conduction. [21,22] However, by adding iodine to the ). b) The liquid, viscoelastic and crystalline phases are indicated on the figure for decreasing temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…[19,20] Previously it was found that incorporating the redox couple I /I 3 and higher polyidides into existing gel electrolytes by adding iodine increases the conductivity, which was attributed to Grotthuss conduction. [21,22] However, by adding iodine to the ). b) The liquid, viscoelastic and crystalline phases are indicated on the figure for decreasing temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these problems, many research groups have been searching for alternatives to replace the liquid electrolytes, such as inorganic or organic hole conductors, 2-4 ionic liquids, 5,6 polymer 7-9 and gel electrolytes. [10][11][12][13][14] Our group has been working on DSSC using polymer electrolytes based on copolymers of poly(ethylene oxide) (PEO) derivatives since 1996 and the first results were published in 1999. 15 The best solar energy conversion efficiency obtained for a solid-state DSSC (1 cm 2 of active area) was 2.6% under 10 mW cm -2 and 1.6% under 100 mW cm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion by a physical and bond exchange (Grotthuss) mechanism has been proposed to occur in electrolytes containing the I À /I 3 À redox couple. [13] When both simple physical diffusion and exchange reaction are present, D app can be rationalized by the Dahms-Ruff Equation (1): [14][15][16][17][18] …”
Section: Resultsmentioning
confidence: 99%